What do dermatologists and dermatology residents think about their residency training in dermatology? - Porriño-Bustamante, María Librada; Buendía-Eisman, Agustín; Arias-Santiago, Salvador (Frontiers in Medicine, 2023)
Introduction In Spain, graduates in medicine take a state exam which, depending on their result, enables them choose a speciality in a specific hospital. Becoming a specialist in dermatology involves 4 years of training in a hospital. The content of the speciality is government regulated, although it can vary slightly in different hospitals. Feedback about this training period could provide key information to improve any failings. The aim of the study was to evaluate the perspectives of dermatologists and dermatology residents toward residency training. Materials and methods Resident dermatologists in their final 2 years and recently qualified dermatologists answered a survey regarding the residency, and personal perspectives and objectives within dermatology. Results A total of 54 participants answered the survey. Their mean age was 29.26 years old. Around 74% of them had had at least 3 clinical sessions per week during their residency and 87% of them considered these clinical sessions to have been useful for their training. The main shortcomings in their training were perceived as laser and esthetics, followed by trichology then research and contact dermatitis. However, 85.2% of them had done external rotations to progress in the areas they felt they needed to improve. Around 55% of the participants had considered specializing in research. Regarding research doctorates, 20.4% were doing their PhD or had already finished it, and of the remaining, 62.79% were interested in doing one. Conclusion The opinions, feelings and aspirations of the dermatology residents are an important barometer for the future of the speciality. Training in research, laser and esthetics was perceived as a weakness by the participants, while clinical sessions and external rotations were considered good for their training. The information from this survey establishes a reference point from which present needs and future trends can be gauged.